Cardiopulmonary exercise testing in the assessment of pulmonary hypertension. (April 2011) - Arena, Ross; Guazzi, Marco; Myers, Jonathan; Grinnen, Daniel; Forman, Daniel E; Lavie, Carl J
The assessment of patients with suspected or confirmed pulmonary arterial hypertension (PAH) and secondary pulmonary hypertension (PH) continues to evolve and, in recent years, evidence demonstrating that cardiopulmonary exercise testing (CPX) provides valuable information has grown at an impressive rate. The key premise supporting the use of CPX is that certain variables obtained provide insight into the degree of ventilation/perfusion mismatching secondary to altered pulmonary hemodynamics. In this article, we discuss the pathophysiology of PAH and secondary PH and its impact on cardiac function, review the clinical presentation of patients with elevated pulmonary pressures and outline a case for the use of CPX as an integral assessment technique, discuss CPX technology and testing procedures, and review the current state of available evidence and provide clinical recommendations for CPX in the setting of known or suspected PAH and secondary PH.